2018
DOI: 10.1186/s12903-018-0632-1
|View full text |Cite
|
Sign up to set email alerts
|

The Oral health status of children with autism Spectrum disorder in KwaZulu-Nata, South Africa

Abstract: BackgroundEchoing the sentiments of the Sixty-seventh World Health Assembly of May 2014, mandating the all-inclusive and synchronized efforts for the management of autism spectrum disorder (ASD), the aim of this current study was to investigate the oral health status of children with ASD aged between 7 to 14 years in KwaZulu-Natal, South Africa.MethodsAn investigative cross-sectional quantitative design employing non-probability purposeful sampling was conducted on 149 children with ASD attending special needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
3
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 42 publications
7
26
3
12
Order By: Relevance
“…The results for the oral hygiene status in children with autism are largely controversial, varying from very good to very poor. Several studies have reported good oral hygiene in participants with ASD [9,[26][27][28], but others have indicated poor oral hygiene [29][30][31][32], which was also supported by our results.…”
Section: Resultssupporting
confidence: 91%
“…The results for the oral hygiene status in children with autism are largely controversial, varying from very good to very poor. Several studies have reported good oral hygiene in participants with ASD [9,[26][27][28], but others have indicated poor oral hygiene [29][30][31][32], which was also supported by our results.…”
Section: Resultssupporting
confidence: 91%
“…The observed male/female ratio (which is approximately 4:1) is in agreement with values reported by the WHO based on which ASD is 3 to 4 times more frequent in males than in females [1]. The overall caries prevalence in our study is 66.4%, smaller than the one reported in similar studies in South Africa and United Arab Emirates [20,27] (where a prevalence up to 85% was observed) but (more than 20%) larger than the prevalence that appears in other studies for Turkey and India [22]. In terms of caries severity, the average DMFT/dmft score for our sample (2.91) is substantially smaller than the one obtained in comparable studies conducted in Africa [24,27] (where average values of DMFT/dmft of 4.79 and 7.23 have been found), slightly smaller than the one reported in a similar study in Turkey [36] and slightly larger than those obtained in studies on autism in Asian populations [20,21,[36][37][38] (for which an average value between 2.01 and 2.4 has been reported).…”
Section: Discussionsupporting
confidence: 91%
“…The overall caries prevalence in our study is 66.4%, smaller than the one reported in similar studies in South Africa and United Arab Emirates [20,27] (where a prevalence up to 85% was observed) but (more than 20%) larger than the prevalence that appears in other studies for Turkey and India [22]. In terms of caries severity, the average DMFT/dmft score for our sample (2.91) is substantially smaller than the one obtained in comparable studies conducted in Africa [24,27] (where average values of DMFT/dmft of 4.79 and 7.23 have been found), slightly smaller than the one reported in a similar study in Turkey [36] and slightly larger than those obtained in studies on autism in Asian populations [20,21,[36][37][38] (for which an average value between 2.01 and 2.4 has been reported). We found that both caries prevalence and caries severity have a statistically significant association with the type of diet and the periodontal indices PI and GI of the autistic patient but, contrary to the findings of similar studies [12,[36][37][38], a not statistically significant association with age and gender was found.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations